Structural, electrical and optical properties of CdS thin films and the effect of annealing on photoconductivity - Abdul-Ameer Al-Rehamey, Haidar Jwad (Iraqi Journal of Physics, 2019)
Cadmium sulfide (CdS) thin films with n-type semiconductor characteristics were prepared by flash evaporating method on glass substrates. Some films were annealed at 250 oC for 1hr in air. The thicknesses of the films was estimated to be 0.5µ by the spectrometer measurement. Structural, morphological, electrical, optical and photoconductivity properties of CdS films have been investigated by X-ray diffraction, AFM, the Hall effect, optical transmittance spectra and photoconductivity analysis, respectively. X-ray diffraction (XRD) pattern shows that CdS films are in the stable hexagonal crystalline structure. Using Debye Scherrerś formula, the average grain size for the samples was found to be 26 nm. The transmittance of the samples was determined from optical trasmittance spectra. It is observed that the direct band gap energy for as deposited and annealed films are (2.55, 2.45) eV, respectively. The effect of annealing at 250 oC for 1hr in air on optical and photoconductivity of films under various intensity of illuminations (43.81 and 115.12) mW/cm2 was studied. The dark and photocurrents of the annealed films were found to be greater than that of as deposited.